Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/1941738117714160
|View full text |Cite
|
Sign up to set email alerts
|

Association of Competition Volume, Club Sports, and Sport Specialization With Sex and Lower Extremity Injury History in High School Athletes

Abstract: Background:High school athletes are increasingly encouraged to participate in 1 sport year-round to increase their sport skills. However, no study has examined the association of competition volume, club sport participation, and sport specialization with sex and lower extremity injury (LEI) in a large sample of high school athletes.Hypothesis:Increased competition volume, participating on a club team outside of school sports, and high levels of specialization will all be associated with a history of LEI. Girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(133 citation statements)
references
References 18 publications
(48 reference statements)
6
117
2
4
Order By: Relevance
“…The application of the inclusion and exclusion criteria during the full-text review resulted in the exclusion of 7 studies. Two studies were removed because they were not explicitly focused on overuse injury, 24,25 1 was removed because the comparison was between athletes with high specialization in team sports and athletes with high specialization in individual sports, 26 1 was removed because the authors did not directly compare specialized and nonspecialized groups and the measurement of specialization was not clearly defined, 27 and 3 studies were removed because the athletes fell outside of the established age range, 28 -30 leaving 5 studies from which data were abstracted and synthesized in the results.…”
Section: Results Of Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of the inclusion and exclusion criteria during the full-text review resulted in the exclusion of 7 studies. Two studies were removed because they were not explicitly focused on overuse injury, 24,25 1 was removed because the comparison was between athletes with high specialization in team sports and athletes with high specialization in individual sports, 26 1 was removed because the authors did not directly compare specialized and nonspecialized groups and the measurement of specialization was not clearly defined, 27 and 3 studies were removed because the athletes fell outside of the established age range, 28 -30 leaving 5 studies from which data were abstracted and synthesized in the results.…”
Section: Results Of Searchmentioning
confidence: 99%
“…Post et al 24 examined the association between specialization and injury and found that athletes with specialization were more likely to report a history of any type of injury in the previous year. Unfortunately, the authors did not explicitly focus on overuse injury, and we were unable to include this article in the review.…”
Section: Figurementioning
confidence: 99%
“…Currently, a widely used 3-point sport specialization classification system exists to better classify (low, moderate, and high) youth athletes to help quantify and evaluate the risk factors outlined in these recommendations. 9,10,16,17 This classification system has been used to identify an association between highly specialized youth athletes and overuse injuries. The athletes were categorized in the 3-point specialization classification system as either lowly, moderately, or highly specialized, dependent upon their answers or the parents' answers about their child.…”
Section: Methodsmentioning
confidence: 99%
“…9 The consequences of sport specialization include overuse injuries and burnout. 1,4,6,[8][9][10][11][12] These consequences have prompted various medical organizations to release position statements warning against sport specialization, as well as recommending the need for more research on the limited data supporting these recommendations. 1,7 These recommendations include time-based measurements for sport participation-such as months per year and hours per week, as well as avoiding participating in multiple leagues at the same time-to provide guidelines for youth athletes in organized sport to help prevent overuse injury.…”
mentioning
confidence: 99%
“…This approach to training is highly controversial; recent literature suggests that this type of specialized training may increase the rate of acute injuries, overuse injuries, and ultimately lead to decreased sports participation. [2][3][4] Sports which require high velocity movement and change of direction demands, for example alpine skiing, can lead to lower extremity overuse injuries. 5,6 Anterior knee pain (AKP) is a common complaint in youth athletes.…”
Section: Introductionmentioning
confidence: 99%